Stakeholder attitudes on AI integration in ophthalmology = Einstellungen der Stakeholder zur KI-Integration in der Ophthalmologie - Saad, Amr; Turgut, Ferhat; Becker, Matthias D.; DeBuc, Delia; Somfai, Gabor Mark (Klinische Monatsblätter für Augenheilkunde, 2025)
Artificial intelligence (AI) is gaining widespread traction in ophthalmology, with multiple screening and diagnostic tools already being approved by U. S. and EU authorities. However, the adoption of these tools among medical professionals and their acceptance among patients is still questionable. This narrative review analyses the current literature on stakeholder perspectives on the integration of AI in ophthalmology, with a focus on comparing views across different global healthcare contexts. A PubMed search was conducted for original research articles published between January 1, 2015 and August 31, 2024. The analysis revealed different levels of acceptance for different AI applications among different stakeholder groups. Ophthalmologists and optometrists generally showed positive attitudes toward AI as an adjunct tool, while patients expressed mixed views, appreciating potential benefits while expressing concerns about a lack of transparency in the integration of AI into healthcare. This review reveals a complex landscape of stakeholder perspectives on AI in ophthalmology, highlighting the need for tailored approaches to AI implementation that address specific concerns and consider different healthcare contexts. The findings underscore the importance of collaborative efforts to develop context-specific, effective AI solutions in ophthalmology.